Islam and Globalization in the Study of Tafsir Maudhu'i: Islam dan Globalisasi dalam Kajian Tafsir Maudhu’i - Devi Apriliani; Diziddia Tafa; Faqih al Munawwar (Bulletin of Islamic Research, 2024)
In the current era of globalization, any information related to contemporary issues is worthy of research. In this paper, the reviewer will discuss the facts that occur as a result of globalization. Globalization, or social change, is significantly influenced by the Islamic religion. This change will definitely have good or bad effects. In the context of globalization, there are many debates underlying this research. Therefore, the aim of this research is to briefly discuss the debate on globalization. The aim of this research is to determine the position of Islam in relation to globalization and to respond to the position of Islam in the world of globalization. Islam is a perfect religion that will not be lost by time and era. Islam will continue to exist forever and can be a solution to various problems of the times, especially in the era of globalization.